Helical carbon nanofibers-enhanced nickel silicate: An innovative anode material for high-performance lithium-ion batteries - Liu, Yonghong; Jiang, Dongwei; Li, Songquan; Wang, Ziyu; Jin, Yongzhong; Zhang, Zhengquan; Xu, Tao (Electrochimica acta, 2025)
•A novel NiSiO/HCNFs composite was fabricated via a hydrothermal method.•The electrochemical performance of the composite has been significantly enhanced.•HCNFs form a conducting network, enhancing electrochemical performance. Metal silicates are considered promising candidates for anode materials in lithium-ion batteries (LIBs) due to their excellent energy storage capability, natural abundance and eco-friendly characteristics. However, their practical application has is significantly impeded by weak electron transport efficiency and structural expansion/contraction during lithium-ion insertion/extraction. In this research, a layered nickel silicate/helical carbon nanofiber (NiSiO/HCNFs) nanocomposite is successfully synthesized through a straightforward hydrothermal approach and employed as anode material for LIBs. The composite exhibits superior electrochemical performance. At a current density of 200 mA/g, it achieves an initial discharge specific capacity of 1671.04 mAh/g and maintains 774.87 mAh/g after 100 cycles, which are approximately 3.4 and 2.9 times higher than those of HCNFs (225.89 mAh/g) and NiSiO (259.06 mAh/g), respectively. These enhancements are primarily attributed to the synergistic interaction between HCNFs and NiSiO. Specifically, the unique three-dimensional helical structure of HCNFs provides mechanical stability, effectively mitigating the volume changes of NiSiO during charge/discharge processes. Meanwhile, the HCNFs improve electrical conductivity, enhance Li⁺ diffusion kinetics, and reduce charge-transfer impedance. This study demonstrates the potential of HCNFs as a structural and conductive support, offering valuable insights for the design of high-performance anode materials. [Display omitted]